Gardens and Academies in Early Modern Italy and Beyond - Ribouillault, Denis, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
This collection of essays explores the role of gardens in early modern academies and, conversely, the place of what might be called 'academic culture' in early modern gardens. While studies of botanical gardens have often focused on their association with a research institution, the intention of this book is deliberately broader, seeking to explore the interactions and intersections between the built environment of the early modern garden and the more or less organised social and intellectual life it supported. As such, the book contributes to the intersection of several fields of research: garden history, literary history, architectural history and socio-political history, and considers the garden as a site of performance that requires an intermedial approach.